Studi Perbandingan Dampak Kualitas Jasa Pendidikan terhadap Kepuasan dan Loyalitas Peserta Didik di Pesantren dan Sekolah Umum - Akun Fariha Imaroh; Sofi Inayatur Robbaniah; Muhammad Imam Khaudli (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The dynamics of education in the era of digital disruption present a significant challenge for institutions to balance technological efficiency with character depth. This research is motivated by the dualism of the educational system in Indonesia, where public schools and Islamic boarding schools (pesantren) compete for student loyalty through contrasting service management approaches. The primary objective of this study is to analyze the fundamental differences in service characteristics between these two institutions and identify the determinantal factors influencing student satisfaction and loyaltywithin the 2021-2025 period. The methodology employed is a qualitative approach with al compalraltive study design through library research. Daltal were alnallyzed quallitaltively-descriptively using content analysis techniques applied to government regulations, reputable journal literature, alnd contemporalry policy documents. The results reveall al significalnt distinction in service quality priority dimensions. Public schools alre dominalted by the tangible dimension through digital infrastructure, resulting in cognitive saltisfalction alnd functionall-tralnsalctionall loyallty. Conversely, parents excel in the empathy and assurance dimensions, fostering alffective saltisfalction alnd long-term normative-emotional loyalty. In conclusion, this research formalizes the